BISNIS DALAM PERSPEKTIF UNDANG-UNDANG No.33 TAHUN 2014 - Mospa Darma; elyani elyani (VALUE, 2021)
In the business world, in meeting the needs of producers where producers must race, which has become a benchmark for the economic doctrine where supply depends on demand and demand is based on the interests of society, but all market needs are determined by demand. regulations imposed by manufacturers and governments. get around the market formula for satisfaction, hygiene, health with the maximum content contained in halal products. Legislation implemented by the Government with reference to Law number 33 of 2014 provides limits on legal certainty for consumers.